Brace stiffness for parallel semi-rigid columns. (April 2022) - Zhang, Linbo; Ma, Terence; Xu, Lei
Abstract : Highlights: The proposed method evaluates the ideal brace stiffness of a system consisting of semi-rigid parallel columns. A novel unbraced frame model is proposed to account for the effect of axial compressive load on column stiffness. Lateral stiffness interaction among parallel columns is explicitly considered in the derivation of ideal brace stiffness. The effect of column flexibility on the mid-height deflection of a semi-rigid column is assessed. The effect of different column lateral stiffnesses needs to be considered in determining the ideal brace stiffness. Abstract: Proposed in the paper is an analytical method of determining the ideal brace stiffness for a structural system consisting of parallel semi-rigid columns with horizontal tie bracing at mid-height. Based on a newly proposed unbraced frame model, the ideal brace stiffness of the parallel column system can be obtained from buckling of an equivalent unbraced frame with column height being half of the original one. The influence of column stiffness interaction associated with semi-rigid connections, column sizes, and applied loads is theoretically considered in the determination of the ideal brace stiffness, which makes the proposed method applicable to systems with nonidentical columns. For a system with the same columns and end connections, the minimum ideal brace stiffness in elastic analysis can be achieved with the end-fixity factor being 0.392. In addition, a simple expression is presented to quantify the effect of the semi-rigid connection on the ideal brace stiffness of the system. Good agreements between analytical and finite element analysis results of presented examples indicate the proposed method can accurately evaluate the ideal brace stiffness of a semi-rigid parallel column system.